Strengthening Religious Moderation through Islamic Religious Education in Indonesian Universities: A Case Study at Yogyakarta State University - Marzuki; Sulthon Abdul Aziz; Fungki Febiantoni (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
This research investigates the reinforcement of religious moderation through Islamic Religious Education (IRE) at Yogyakarta State University. Employing a qualitative case study approach, the study engaged IRE lecturers and students through observations, interviews, and focus group discussions. Data were analyzed using the Miles and Huberman interactive model. The findings reveal that religious moderation has been successfully implemented, with tasamuh (tolerance) and tawassuth (moderation) emerging as the core values. However, despite high foundational understanding, a cognitive gap persists among a minority of students regarding non-violence. The study concludes that strengthening religious moderation requires a shift from lecturer-centric delivery to a systematic, technology-integrated academic culture. Effective pedagogical strategies identified include collaborative project-based learning and contextual discussions. These results underscore the necessity for innovative teaching materials and structured assessments to bridge conceptual gaps. Consequently, integrating moderation values into the university's broader institutional framework is essential for sustainable character development in higher education.